The issue of using unmanned aerial vehicles during armed conflicts in the 21st century - Małodobry, Zbigniew; Nastaj-Sałek, Karolina; Cyrkun, Katarzyna; Jakubiec, Wojciech (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The article analyzes the growing role of drones inmodern military operations and their impact on modernbattlefields. The aim of the article was to present the evolution ofunmanned aerial vehicle technology, their application in varioustypes of armed conflicts and to identify key challenges related totheir use. The research was conducted by analyzing literature,reports and international documents. The article discusses threemain aspects of the use of unmanned aerial vehicles. The workfocuses on the genesis and development of drone technology, presenting their first intelligence applications and their latertransformation into a key combat tool. The article analyzes thecontemporary applications of unmanned aerial vehicles, taking into account their importance in asymmetric, hybrid and specialoperations. Attention is paid to their role in intelligence collection,precision attacks and military logistics. The work also focuses onthe future of drones, the development of autonomous technologiesand the legal and ethicalchallenges resulting from their use.Particular emphasis is placed on the problems of responsibility forcombat decisions and the risks associated with the autonomy of systems based on artificial intelligence.